Legal Analysis Of The Authority Of A Notary Related To Making A Binding Deed Of Sale And Purchase (Case Study: Supreme Court Decision Number 685/Pdt.G/2020/PN Mdn) - Fandi Andremon Manahan Situngkir (International Journal Of Humanities Education and Social Sciences (IJHESS), 2023)
This study raised the issue of the deed of binding sale and purchase of land handed down to the heirs of the buyer but the certificate and deed that has been approved by the notary was lost and a few years later there are parties who recognize that the object of land owned by the buyer has changed hands without the knowledge of the first buyer. The case is contained in the Supreme Court Decision No. 685/Pdt.G / 2020 / PN Mdn. The problem arises starting from Jan Willem Roeloffs as Plaintiff I and Pieter Roeloffs as plaintiff II intends to take care of the deeds he has related to the purchase of agricultural land covering an area of 2891 m2 located in Jaranguda Village, Simpang Empat District, Karo Regency, which his late parents did by borrowing the name of an Indonesian citizen, namely on behalf of Betty Boru Saragih as described in title certificate No. 88 dated November 7, 1995 and in the binding sale and purchase by the second party who has completed the payment of the purchase price to the First party of Rp. 10.000.000, - (ten million rupiah) by using deed of sale and purchase No. 6 dated January 12, 2001 as proof of receipt of payment by the First party. However, on September 16, 2006, the plaintiffs ' father died so that the obligation to take care of the Certificate of property rights number 88 dated November 7, 1995 an Betty Boru Saragih fell on the plaintiffs. On February 3, 2007. the plaintiffs asked the notary on behalf of Haji Marwansyah Nasution to take care of and reverse the name of property rights Certificate Number 88 dated November 7, 1995 on behalf of Betty to be on behalf of the plaintiffs by submitting the original document in 2012, there is someone who claims to be the owner of property rights Certificate Number 88 dated November 7, 1995 an Betty Boru Saragih based on The Binding Of Sale and Purchase With Tigor Manurung described in The Binding Of Sale and purchase with the right to repurchase number 228 dated September 23, 2011 made before notary Martua Simanjuntak SH. With these events, The plaintiffs objected and were aggrieved because according to the plaintiffs the original documents submitted to notary Haji Marwansyah Nasution had been abused by the Haji Marwansyah Nasution and Notary Martua Simanjuntak SH by issuing power of Attorney No. 68 dated November 30, 2010 from Betty Boru Saragih to Tigor Manurung made before Notairs Haji Marwansyah Nasution which was used as the basis for the sale and purchase of Tigor belongs to no. 88 dated November 7, 1995 as a result of the actions of Notary Haji Marwansyah Nasution and his team along with Notary Martua Simanjuntak who reversed the name of the Certificate of property rights No. 88 dated November 7, 1995 an Betty Boru Saragih became an Hotman Simanjuntak without the consent and without the knowledge of the plaintiffs who had the original land certificate, the plaintiffs filed a lawsuit against the defendants as stated in Supreme Court decision number 685/Pdt.G / 2020 / PN Mdn. In the decision, the panel of judges granted the plaintiff's claim I and II in part and sentenced the defendant to pay forced money (dwangsom) after this decision has permanent legal force.